Dirac Generalized Relativistic Quantum Wave Function which Gives Right Electrons Number in Each Energy Level by Controlling Quantized Atomic Radius (Global Journal of Science Frontier Research, 2020)
Using generalized special relativistic energy-momentum relation the linear energymomentum Dirac relation was obtained. This equation was used to find Dirac generalized relativistic quantum equation. This equation was used to find the probability and the number of particles for each atomic energy level. The wave function found using this equation can give an expression for the number of electrons in each energy levels if the atomic radius is quantized and satisfy a certain relation.
Keywords: generalized special relativity; dirac equation; atomic energy levels; number of electrons in the energy level; atomic radius